Risk factors for perinatal death in two different levels of care: a case-control study - Silveira Soares Moura, Paula Maria [UNESP]; Maestá, Izildinha [UNESP]; Rugolo, Ligia Maria Suppo de Souza [UNESP]; Ramos Berbel Angulski, Luis Felipe [UNESP]; Caldeira, Antonio Prates; Peraçoli, José Carlos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Biomed Central Ltd., 2014)
Background: According to the World Health Organization, there are over 6.3 million perinatal deaths (PND) a year worldwide. Identifying the factors associated with PND is very helpful in building strategies to improve the care provided to mothers and their babies.Objective: To investigate the maternal, gestational and neonatal factors associated with PND at two different levels of care.Methods: Case-control study including 299 PND cases and 1161 infants that survived the early neonatal period (controls) between 2001-2006 in two hospitals at different care levels (secondary and tertiary) located in southeastern Brazil. Correlations between study variables and PND were evaluated by univariate analysis. PND-related variables were included in a multiple logistic regression model, and independent estimates of PND risk were obtained.Results: Although five-minute Apgar score <7, low birthweight and maternal hemorrhage were associated with PND in the secondary care center, no independent risk factors were identified at this level of care. In the tertiary hospital, PND was positively associated with primiparity, male sex, prematurity, low 5-minute Apgar score, and pregnancy complicated by arterial hypertension or intrauterine infection.Conclusions: Several risk factors positively associated with PND were indentified in the tertiary, but not in the secondary care level hospital. Since most of the risk factors herein identified are modifiable through effective antenatal and intrapartum care, greater attention should be given to preventive strategies.
Keywords: Perinatal death; Risk factors; Care levels; Maternity